THE RELATIONSHIP BETWEEN INTELLECTUAL, EMOTIONAL AND SPIRITUAL INTELLIGENCE WITH PHYSICAL EDUCATION TEACHER PERFORMANCE - Thaib, Armia (Sport Pedagogy Journal, 2024)
The performance of a teacher, including physical education teachers, can be related to the intellectual, emotional and spiritual intelligence of the teacher concerned. This study aims to determine the relationship between intellectual, emotional and spiritual intelligence with the performance of physical education teachers. The population and research sample of physical education teachers of public high schools in Pidie Regency amounted to 22 people. Data collection techniques using the instrument intellectual, emotional, spritiual and teacher performance.Data analyzed by product moment correlation test. The results showed that in general physical education teachers in Pidie Regency have high intellectual intelligence. emotional intelligence and spiritual intelligence are high and also high emotional intelligence and have good performance. Intellectual intelligence with performance correlation coefficient value (r) 0.640, emotional intelligence with performance correlation coefficient value (r) 0.574, spiritual intelligence with performance correlation coefficient value (r) 0.682. Simultaneously emotional intelligence, intellectual and spiritual intelligence have a significant relationship with the performance of physical education teachers in Pidie Regency. This is indicated by the correlation coefficient value (r) 0.760.Keywords: Teacher Performance, Intellectual, Emotional, Spiritual Intelligence